2020
DOI: 10.1590/1806-9282.66.12.1633
|View full text |Cite
|
Sign up to set email alerts
|

Pain and anxiety in office histeroscopy

Abstract: SUMMARY BACKGROUND: Anxiety is almost always present before medical interventions and may play a role in pain perception. We aim to evaluate factors associated with pain intensity reported by patients submitted to Office Hysteroscopy (OH). METHODS: Cross-sectional observational study, with data from April to November 2015. It included patients attended at the Assis Chateaubriand Maternity School (MEAC/UFC) with an indication of office hysteroscopy. Before the examination, the patients answered a validated qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…It is worth mentioning that the degree of pain experienced by the patient is determined by many factors, such as technical aspects, experience of the operator, ab- normalities of the reproductive organs, the total duration of the procedure, and the psychological profile of the patient [10,34,45,46]. A similar relationship was observed in the present study: patients in the RRO group reported more severe pain with the increase in the duration of the procedure.…”
Section: Discussionsupporting
confidence: 83%
“…It is worth mentioning that the degree of pain experienced by the patient is determined by many factors, such as technical aspects, experience of the operator, ab- normalities of the reproductive organs, the total duration of the procedure, and the psychological profile of the patient [10,34,45,46]. A similar relationship was observed in the present study: patients in the RRO group reported more severe pain with the increase in the duration of the procedure.…”
Section: Discussionsupporting
confidence: 83%
“…23,24 The Pipelle biopsy for endometriosis (PBEM) is inexpensive, less invasive and can be conducted in outdoor settings, and beyond these benefits it also has a risk of failing to obtain adequate sample. 22 Many procedures of sampling cause anxiety and stress among women 25 , but PBEM is being tolerated well by most of the women in comparison to other similar setting techniques. 26 This study is conducted to see the efficacy of PBEM for acquiring adequate sample in outdoor settings for pathology and to report the morphology of sample taken.…”
Section: Introductionmentioning
confidence: 99%
“…Impact of pain on the biopsy’s success remains underestimated and there are only a few reports of inconclusive results [ 14 , 19 , 20 ]. Considering that the relationship between Pipelle sampling and pain in patients undergoing endometrial biopsy for AUB has not been established yet, the aim of this study was to investigate factors influencing it.…”
Section: Introductionmentioning
confidence: 99%